Methylation in MIRLET7A3 Gene Induces the Expression of IGF-II and Its mRNA Binding Proteins IGF2BP-2 and 3 in Hepatocellular Carcinoma - Waly, Amr A.; El-Ekiaby, Nada; Assal, Reem A.; Abdelrahman, Mohamed M.; Hosny, Karim A.; El Tayebi, Hend M.; Esmat, Gamal; Breuhahn, Kai; Abdelaziz, Ahmed I. (Frontiers in Physiology, 2019)
miR-let-7a is a tumor suppressor miRNA with reduced expression in most cancers. Methylation of MIRLET7A3 gene was reported to be the cause of this suppression in several cancers; however, it was not explicitly investigated in Hepatocellular Carcinoma (HCC). We aimed at investigating miR-let-7a expression and molecular mode in HCC, identifying drug-targetable networks, which might be affected by its abundance. Our results illustrated a significant repression of miR-let-7a, which correlated with hypermethylation gene of origin MIRLRT7A3. This was further supported by the induction of miR-let-7a expression upon treatment of HCC cells with a DNA-methytransferase inhibitor. Using a computational approach, insulin-like growth factor (IGF)-II and IGF-2 mRNA binding proteins (IGF2BP)-2/-3 were identified as potential targets for miR-let-7a that was further confirmed experimentally. Indeed, miR-let-7a mimics diminished IGF-II as well as IGF2BP-2/-3 expression. In conclusion, this study suggests that DNA hypermethylation leads to epigenetic repression of miR-let-7a in HCC cells, which, induces the oncogenic IGF-signaling pathway.